EVOLUÇÃO PALEOAMBIENTAL DA DEPRESSÃO DE ABROLHOS (ES, BRASIL) BASEADO NA DISTRIBUIÇÃO DE FORAMINÍFEROS BENTÔNICOS - Ruschi, Anita Gomes (2022)
The post-last glacial maximum transgression was marked by secular climate fluctuation events that directly influenced paleoenvironmental evolution on global continental shelves. During the transgression, cooling events such as the Younger Dryas (YD) and rapid melting events such as Meltwater Pulse (MWP), among others, played an important role in varying the rates of relative sea level rise, as well as in the formation of coastal environments. The focus of this study is the south shelf of Abrolhos, which is marked by a feature known as the Abrolhos Depression (AD), having previously been described as a paleolagoon. The objective of this study is to investigate the formation of this paleolagoon and the paleoenvironmental variations that it was submitted to during the marine transgression in the last 18 thousand years. The study was conducted using a core located in the center of the DA, collected at a depth of 63 m. The main focus of the paleoenvironmental analysis was based on the identification of benthic foraminifera and carbon 14 data, in addition to the use of previously available geochemical proxies. The results showed that throughout the core, there were 85 classified taxa, of which 69 being at the hierarchical level of species, and 16 at the hierarchical level of genus. It was possible to divide the core into 4 Biofacies based on the assemblages of benthic foraminifera: the Biofacies CH gather samples from the base, 288 to 251cm, and the dominant species of this group were found to be the Cribroelphidium sp. and the Hanzawaia boueana. The Biofacies At brings together samples from 241 to 111cm, WHERE the dominant species is the Ammonia tepida. Another common species in this group is the Cribroelphidium excavatum. The Biofacies AC gathers samples from 101 to 41cm, WHERE the dominant species are the A. tepida and the C. excavatum. The Biofacies HQ brings together the top samples, 31 to 2 cm, WHERE the dominant species are the H. boueana and the Quinqueloculina lamarckiana. From the analysis of foraminifera assemblages, the paleoenvironmental evolution of the AD can be reviewed to be pointing to the following model: The base of the core indicates the presence of carbonate concretions that can compose a karstic ravine surface. The deposition of the Biofacies CH occurs on this surface and suggests marine influence and the beginning of the formation of the paleolagoon around 13,000 years BP. The formation of the DA occurs during the YD and it presents two distinct phases in terms of sedimentation and circulation in the lagoon environment. At first, between 12800 and 12500 cal years B.P., the lagoon is characteristically confined with less circulation, and from around 12,500 years onwards there is an increase in the lagoon circulation, marked by an increase in the density, richness, and diversity of benthic foraminifera. The end of the YD is marked by a significant change in the Biofacies, WHERE the organisms point to a shallow marine environment (Biofacies AC), which is corroborated by all sedimentological and geochemical proxies. This paleoenvironmental change is associated with MWP-1B. With the continuous rise in sea level, the environment becomes open marine, but there is still a change at around 8000 years B.P., which definitively marks the presence of organisms typical of the outer shelf, that is, from depths greater than 50m.